Direct localization of detergents and bacteriorhodopsin in the lipidic cubic phase by small-angle neutron scattering. (2021) - IV, Thomas Cleveland; Blick, Emily; Krueger, Susan; Leung, Anna; Darwish, Tamim; Butler, Paul
No abstract available